PERLINDUNGAN HUKUM TERHADAP INVESTOR DALAM PERDAGANGAN OBLIGASI SECARA ELEKTRONIK - Sudaryanti, Kadek Devi; Darmawan, Ni Ketut Supasti; Purwanti, Ni Putu (Kertha Wicara : Journal Ilmu Hukum; Vol.2, No.1 Edisi Februari 2013)
Capital market is a meeting between the parties who have surplus funds and those who need funds by trading securities. Capital market can as the market to trade securities which already worth more than a year such as stocks and bonds. Bonds are offered to the community through public bidding. The activity of capital market is leading towards a scripless trading. Bond is one of the scripless trading stock forms which has been converted into electronic form. The existence of scripless trading is expected to create efficient capital market, faster transaction dealing and evenly distribution of information. Thus, the quality of the investment climate will be more favourable, because of the high trust of all related parties. Investor is the most important role in capital market. It could be said that the existence of capital market investors is one of the most important indicators.
Keywords: Capital Market, Bonds, Electronic, Investor